Optimization of the Management of Zakat, Infaq, and Shadaqah Funds at the BAZNAS Kabupaten Bojonegoro - Adinda Pramesti Indah Cahyani; Taufiqur Rahman (MALIA: Jurnal Ekonomi Islam, 2023)
This research aims to find out how optimal and what the zakat management strategy has been carried out by BAZNAS Kabupaten Bojonegoro. This research uses a qualitative research method with a field study approach, with the primary data from BAZNAS Kabupaten Bojonegoro and secondary data comes from other literature. The results of this research are that BAZNAS Kabupaten Bojonegoro, in optimizing zakat, infaq, and shadaqah funds, has 5 reception services and 5 distribution programs. The collection strategy is traditional and modern methods, then the distribution strategy places more emphasis on 5 distribution programs. So it can be said that the management of zakat, infaq, and shadaqah funds that has been carried out is almost optimal, marked by the achievement of the management targets that have been set. In this research, what differentiates it from other research is that it lies in the research object and also the research topic studied.